Asymmetry of peripapillary retinal blood vessel and retinal nerve fiber layer thickness between healthy right and left eyes - Quach, Jack; Sharpe, Glen P.; Demirel, Shaban; Girkin, Christopher A.; Mardin, Christian Y.; Scheuerle, Alexander F.; Burgoyne, Claude F.; Chauhan, Balwantray C.; Vianna, Jayme R. (Investigative ophthalmology & visual science, 2023)
The purpose of this study was to determine if there is asymmetry in retinal blood vessel (RBV) position and thickness between right and left eyes (R-L) and evaluate whether R-L asymmetry in RBV thickness is related to R-L asymmetry of retinal nerve fiber layer thickness (RNFLT). We analyzed peripapillary circle scan optical coherence tomography (OCT) examinations from healthy White subjects to measure RNFLT and RBV thickness and position relative to the fovea to Bruch's membrane opening axis, for all visible RBV. The R-L asymmetries of RNFLT and RBV thickness were computed for each A-scan. Four major vessels (superior temporal artery [STA] and superior temporal vein [STV], inferior temporal artery [ITA], and vein [ITV]) were identified using infrared images. We included 219 individuals. The mean (standard deviation) number of RBV measured per eye was 15.0 (SD = 2.2). The position of the STV and STA was more superior in left eyes than in right eyes, by 2.4 degrees and 3.7 degrees, respectively (P < 0.01). There was no region with significant R-L asymmetry in RBV thickness. RNFLT was thicker in right eyes in the temporal superior region and thicker in left eyes in the superior and nasal superior regions, with the asymmetry profile resembling in a “W” shape. This shape was also present in post hoc analyses in two different populations. The R-L asymmetries of RBV and RNFLT at each A-scan were not significantly associated (P = 0.37). There is little R-L asymmetry in RBV, and it is not related to RNFLT asymmetry. This study suggests that R-L RNFLT asymmetry is due to factors other than RBV.